Dyplomacja Drugiej Rzeczpospolitej : z dziejow polskie sluzby zagraniczej - Lossowski, Piotr (Warszawa : Wydawn. Sejmowe, 1992)
A study of the Polish diplomatic relations with other nations, from 1919 to 1939.
Includes bibliographical references (p. 281-[283]) and index.
Keywords: Diplomatic and consular service, Polish; Poland -- Foreign relations -- 1918-1945.